2010
DOI: 10.1186/1743-422x-7-287
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Human Herpes Virus 6 (HHV6) in pediatric lymphomas: impact on clinical course and association with cytomegalovirus infection

Abstract: BackgroundActivation of herpes virus 6 (HHV6) has seen in Hodgkin's and non-Hodgkin's Lymphoma (HL&NHL) as a result of lymphoma associated immunosuppression. Multiple studies have suggested an association between both HHV6 and cytomegalovirus CMV for development of CMV disease affecting the pathogenesis of lymphoma. Therefore, this study investigated the frequency of HHV6, its impact on clinical manifestations of lymphoma and its possible association with risk for development of CMV infection in pediatric lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…This updated analysis of our initial study, which showed an association of CMV reactivation with prolonged hospitalization or death (12), advances understanding of particularly high-risk patient groups by considering HHV-6 in the models. Increased rates of adverse events in patients with co-reactivation of HHV-6 and CMV have been reported in other settings and are speculated to be due to mechanistic interactions between the two viruses (28, 29). …”
Section: Discussionmentioning
confidence: 92%
“…This updated analysis of our initial study, which showed an association of CMV reactivation with prolonged hospitalization or death (12), advances understanding of particularly high-risk patient groups by considering HHV-6 in the models. Increased rates of adverse events in patients with co-reactivation of HHV-6 and CMV have been reported in other settings and are speculated to be due to mechanistic interactions between the two viruses (28, 29). …”
Section: Discussionmentioning
confidence: 92%
“…The impact of most viruses on the pathogenesis of HL remains highly speculative. The presence of virus can be a consequence of immune suppression and subsequent virus reactivation in HL patients [21]. In agreement with this concept, presence of EBV in tumor cells has no significant impact on treatment results, but elevated levels of EBV DNA in the plasma at diagnosis correlates with inferior failure-free survival [22].…”
mentioning
confidence: 90%
“…In the study by Sumiyoshi et al , HHV6 was found in about 50%–68% of patients with malignant lymphomas [25]. It can cause latent infection and subsequent reactivation during immunosuppression [26]. HHV was first reported as human lymphotropic virus, while further studies revealed its presence in some human tumours, especially paediatric lymphomas in association with CMV virus [2628].…”
Section: Discussionmentioning
confidence: 99%
“…This virus is considered as an important opportunistic infection [26]. Presence of CMV in congenital tumours has also previously been reported, suggesting its role in some neonatal sarcomas’ progression [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation